Anjali posted an Question
August 12, 2021 • 20:45 pm 30 points
  • UGC NET
  • Computer Science & Applications

Find the conclusion using the following premises -p aq, r>p, r s, st

Find the conclusion using the following premises -p aq, r>p, r S, st

1 Answer(s) Answer Now
  • 0 Likes
  • 1 Comments
  • 0 Shares
  • Neha tarar best-answer

    The premises are : ¬р^q, r→p, ¬r→s, s → t so the conclusion will be "t". Apply the following rules of inference.

    cropped391873105.jpg
    eduncle-logo-app

    Mam please explain in detail. I did not get it

    eduncle-logo-app

    Firstly, we can apply Simplification rule on premise (1) (¬p∧q) →¬p [5]. Next, we can apply Modus Tollens rule on premise (2,5) (¬p ∧(r →p))→¬r [6]. Next, we can apply Modus Ponens rule on premise (3,6) (¬r ∧ (¬r →s)) → s [7]. Similarly, we can apply Modus Ponens rule on premise (4,7) (s ∧ (s →t)) → t [8]. Hence, we will get t as conclusion.

whatsapp-btn

Do You Want Better RANK in Your Exam?

Start Your Preparations with Eduncle’s FREE Study Material

  • Updated Syllabus, Paper Pattern & Full Exam Details
  • Sample Theory of Most Important Topic
  • Model Test Paper with Detailed Solutions
  • Last 5 Years Question Papers & Answers